Social group representation in a diachronic news corpus - Elmerot, Irene (Cambridge elements. Elements in corpus linguistics, 2025)
Equality is a global factor of prosperity in democratic societies. In this Element, thirty years of newspapers and magazines form the basis of an intersectional study on how different social actors are described in Czechia. A bird's eye perspective points to the news being very white male-oriented, but when scrutinising further, some results differ from previous studies, giving insights on linguistic othering and stratification that may be a threat to equality. The methodology can be used for most languages with a sufficient amount of digitised, annotated and available texts. Since more and more text is being gathered to form datasets large enough to answer any question we might have, this Element helps uncover why we should be careful about which conclusions to draw if the words put into the data are not adapted to the relevant register and context. This title is also available as Open Access on Cambridge Core.